Perbandingan Efektivitas Ampas Teh Hitam dan Ampas Teh Hijau sebagai Adsorben Ion Logam Cr (VI) - Rahma Gurroh Muhajjalin; Inayah Agawijaya; Budi Santoso; Joko Suryadi (Jurnal Kimia Fullerene, 2021)
Industrial waste contains various hazardous chemical compounds, such as heavy metals, one of which is chromium hexavalent ion, Cr (VI). Cr (VI) ion is carcinogenic and has toxic effects on humans. A study to treat Cr (VI) ion waste by adsorption using tea dregs has been carried out. Two types of tea dregs, black tea and green tea dregs are used as adsorbents, to compare their adsorption effectiveness. Adsorption effectiveness was determined using the visible-spectrophotometer. Parameters such as pH, adsorbent mass and concentration of Cr (VI) ions were optimized. Study determination of the adsorption isotherm model for each tea dregs included. The results showed that black tea dregs produced greater effectiveness than green tea dregs, with optimum adsorption conditions at pH 2, adsorbent mass of 0,8 grams and Cr (VI) ion concentration of 100 ppm with 99,50% removal efficiency. Meanwhile, green tea dregs produced the optimum adsorption conditions at pH 2, adsorbent mass of 0,4 grams and Cr (VI) ion concentration of 50 ppm with 87,49% removal efficiency. Langmuir adsorption isotherm model is fit for adsorption process by black tea dregs, meanwhile, green tea dregs fit with Freundlich and Langmuir isotherm model.